2011
DOI: 10.1074/jbc.m110.208660
|View full text |Cite
|
Sign up to set email alerts
|

Protein Targeting to Exosomes/Microvesicles by Plasma Membrane Anchors

Abstract: Animal cells secrete small vesicles, otherwise known as exosomes and microvesicles (EMVs). A short, N-terminal acylation tag can target a highly oligomeric cytoplasmic protein, TyA, into secreted vesicles (Fang, Y., Wu, N., Gan, X., Yan, W., Morell, J. C., and Gould, S. J. (2007) PLoS Biol. 5, 1267-1283). However, it is not clear whether this is true for other membrane anchors or other highly oligomeric, cytoplasmic proteins. We show here that a variety of plasma membrane anchors can target TyA-GFP to sites of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
235
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 253 publications
(254 citation statements)
references
References 54 publications
(30 reference statements)
6
235
1
2
Order By: Relevance
“…This sorting mechanism may be consistent with the proposed role of lipid rafts in setting up platforms to concentrate into MVs proteins destined to secretion. 28,56 Finally, processing of Ab 1-42 to Ab 1-40 may even proceed within MVs. Indeed, previous evidence showed that neuron-derived EMVs contain some components of the gsecretase complex, 57 whereas the insulin-degrading enzyme, which proteolyzes Ab 1-42 and Ab 1-40, has been detected among cargo proteins of microglial EMVs.…”
Section: Discussionmentioning
confidence: 99%
“…This sorting mechanism may be consistent with the proposed role of lipid rafts in setting up platforms to concentrate into MVs proteins destined to secretion. 28,56 Finally, processing of Ab 1-42 to Ab 1-40 may even proceed within MVs. Indeed, previous evidence showed that neuron-derived EMVs contain some components of the gsecretase complex, 57 whereas the insulin-degrading enzyme, which proteolyzes Ab 1-42 and Ab 1-40, has been detected among cargo proteins of microglial EMVs.…”
Section: Discussionmentioning
confidence: 99%
“…Already used binding segments include the C1C2 domain of milk fat globule‐EGF factor 8 protein,105, 106 the transmembrane domain of platelet‐derived growth factor receptor,107 and the extraexosomal N‐terminal of Lamp2b 20. Another method is called the “membrane‐anchored method” and involves anchoring the “cargo” protein to the membrane by fusing it to oligomeric membrane‐anchored proteins instead of certain EV‐related proteins 108. This method has been used in anchoring green fluorescent protein to EVs 108.…”
Section: Modular Design Of Surface Proteinsmentioning
confidence: 99%
“…Another method is called the “membrane‐anchored method” and involves anchoring the “cargo” protein to the membrane by fusing it to oligomeric membrane‐anchored proteins instead of certain EV‐related proteins 108. This method has been used in anchoring green fluorescent protein to EVs 108. Conceptual diagrams outlining these methods are shown in Figure 6 .…”
Section: Modular Design Of Surface Proteinsmentioning
confidence: 99%
“…EVs are relatively easy to control and highly versatile in terms of their surface engineering and cargo encapsulation [32,33]. They are expected to have therapeutic effects against various membrane defect-related diseases, and molecules attached to the EV surface have been shown to confer targeting ability, exhibit increased expression levels, offer enhanced solubility, and trigger antigen immunogenicity [34,35]. In this review, we focus primarily on recent progress in the study of membrane protein-harbouring EVs and discuss the hurdles that must be overcome if we hope to further develop EV-based therapeutics.…”
Section: Introductionmentioning
confidence: 99%